(untitled) (Archive of Conferences, 2020)
Biologically living organisms live in a state of interaction with the environment. They are strongly influenced by the physical properties of the environment, such as temperature, humidity and air pressure. Although the concepts of density, which we know from the school physics course, are widely used in medicine, they are not taught in biology and chemistry courses in academic lyceums. That is, it is based on the knowledge acquired in the school course. If the student knows in advance what profession he intends to pursue in the future, in what field he will work, then he can study the subject in depth.